Dietary interactions with the bacterial sensing machinery in the intestine: the plant polyphenol case - Ferguson, Lynnette R. (Frontiers in Genetics, 2014)
There are millions of microbes that live in the human gut. These are important in digestion as well as defense. The host immune system needs to be able to distinguish between the harmless bacteria and the pathogens. The initial interaction between bacteria and the host happen through the pattern recognition receptors (PRRs). As these receptors are in direct contact with the external environment, this makes them important candidates for regulation by dietary components and therefore potential targets for therapy. In this review we introduce some of the main PRRs including a cellular process known as autophagy, and how they function. Additionally we review dietary phytochemicals from plants which are believed to be beneficial for humans. The purpose of this review was to give a better understanding of how these components work in order to create better awareness on how they could be explored in the future.